(untitled) (Journal of the College of Basic Education, 2022)
Electronic tests are one of the computer technologies that can be employed to overcome some of the difficulties that could hinder the implementation of traditional (paper-based) tests, or to be employed to provide other channels to increase the student’s academic achievement, consolidate information, and develop the skill of self-learning. The electronic test has been applied in Al-Mansour Institute for Preparing Female Teachers and conducting a questionnaire for that.